Effects of Auditor Attributes on Audit Reporting Lag: Empirical Evidence from Nigerian Service Firms - Muhammad , Maryam Isyaku (Asian Journal of Empirical Research, 2020)
The main objective of this paper is to identify the effect of auditor attributes on the audit report lag of quoted service companies operating in Nigeria. The motivation behind this research is hinged on the lack of consensus in prior studies coupled with the dearth of research in listed service companies. This paper employed a sample of sixteen (16) service companies operating on the floor of the Nigerian stock exchange from 2007 through 2016. The results of the regression technique indicate that longer auditor tenure significantly decreases audit report lag. This finding implies that auditors’ expertise improves in the service industry as their tenure increases. This is in turning will accelerate and enhance the quality of audit work. The study recommends that service companies sustain their existing auditors to a reasonable period to enhance timeliness in the audit report. Timely audit reports will enhance the confidence of users of the financial statements to make good decisions.